COVID-19-induced changes in the workplace, psychosocial work environment and employee well-being: a longitudinal study - Kausto, Johanna; Airaksinen, Juhani; Oksanen, Tuula; Vahtera, Jussi; Kivimäki, Marko; Ervasti, Jenni (OXFORD UNIV PRESS, 2025)
Background: In many workplaces, the coronavirus disease 2019 pandemic changed work arrangements, but there is scarce longitudinal evidence on whether psychosocial work environment and employee well-being were affected.Aims To examine the psychosocial work environment and employee well-being before, during and after the pandemic in relation to pandemic-induced changes (working from home, change to other tasks and team reorganization).
Methods: Survey data from a cohort of 20 944 public sector employees in Finland were collected before (2016-2018), during (2020) and after the pandemic (2022). Multilevel linear and logistic regression was used to examine group differences between the before-during and during-after periods of the pandemic.
Results: Working from home was associated with a small but favourable change in worktime control, organizational justice and social capital (scale 1-5) during the pandemic and after the pandemic (marginal mean difference ranging from 0.02 to 0.09 with 95% confidence intervals [CIs] from 0.01 to 0.10). There was a post-pandemic increase in work time control, even among participants with a transfer into other tasks (0.11, 95% CI 0.07, 0.14) or team reorganization (0.06, 95% CI 0.02, 0.10). The decline in self-rated work ability (scale 0-10) before and during the pandemic was greater in those transferred into other tasks (-0.10, 95% CI -0.13, -0.06) than in those not (-0.05, 95% CI -0.06, -0.04).
Conclusions: Working from home during the pandemic was accompanied by small favourable changes in the psychosocial work environment during the pandemic, whereas transition to different tasks was associated with a decline in self-rated work ability.The aim of this study is to explore how changes in work arrangements may affect the psychosocial work environment and well-being of Finnish public sector employees. Unlike most previous studies, our analyses are based on data collected before, during and after coronavirus disease 2019 pandemic. Working from home during the pandemic was accompanied by small favourable changes in the psychosocial work environment during the pandemic, whereas transition to different tasks was associated with a decline in self-rated work ability.